(untitled) (Revista Contexto & Educação, 2026)
The supervised internship is an opportunity for students during initial training to experience the challenges of the teaching profession in its natural context. In that experience, the supervising teacher plays a fundamental role in integrating the trainees into the school during their internships. Based on this, in this research we sought to characterize the reception conditions offered by supervisors in initial teacher training in a Chemistry degree course, based on the voices of the supervisors themselves. For this purpose, four teachers who usually supervise chemistry trainees were interviewed using semi-structured interviews. The interviews were audio-recorded and later transcribed, giving rise to the empirical data of this research. In analyzing the data, we used the methodological approach of Data-Based Theory, in the version reworked by Strauss and Corbin, which includes the processes of open, axial and selective coding in order to build a substantive theory about the phenomenon under investigation. The results showed that reception is influenced by the distance between the university and the school, as well as the lack of commitment on the part of some trainees. This distancing creates insecurity in supervisors and distrust in the quality of initial training, which has a negative impact on reception. Additionally, supervisors have experienced a feeling of helplessness and work overload during internships. Based on these findings, we highlight the need for public policies that establish the functions to be fulfilled and the appropriate conditions for supervisors in this process.